MEDICINAL PLANT - MELISSA OFFICINALIS - Usmonova Gulshod Ibrohimovna; Nasriddinova Nargiza Zavqiy qizi (Web of Journals Publishing, 2024)
The study of medicinal plants, identifying their properties, and investigating their applications in traditional medicine is one of the pressing issues of our time. This article scientifically substantiates the botanical classification, distribution areas, chemical composition, unique medicinal properties, and uses in traditional medicine of Melissa officinalis - the medicinal lemon balm plant.
Keywords: Melissa officinalis - Medicinal lemon balm, medicinal, concentration, extraction, introducer.